2021
DOI: 10.1016/j.eclinm.2021.101124
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of ALRV5XR in men with androgenetic alopecia: A randomised, double-blinded, placebo-controlled clinical trial

Abstract: Background: Androgenetic alopecia (AGA) is the most common hair loss disorder seen in men. It can have an early onset but has also been associated with ageing and senescence. It often induces pronounced psychological impact. ALRV5XR, a new hair loss treatment herein evaluated, was designed to target multiple molecular pathways involved in hair growth and hair follicle stem cell biology. The main objectives of the study were the assessment of safety and efficacy profiles of ALRV5XR in men. Methods: This 24-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Previously, for ALRV5XR, we reported remarkable and clinically significant increases in TH regrowth when compared to other treatments (1,2). In these studies, both sexes had common TH but highly differential VH densities at baseline (see Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Previously, for ALRV5XR, we reported remarkable and clinically significant increases in TH regrowth when compared to other treatments (1,2). In these studies, both sexes had common TH but highly differential VH densities at baseline (see Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 74%
“…This unique property suggests a novel mechanism of action for ALRV5XR. Interestingly, during induction of hair and skin regeneration, platelet-rich plasma (PRP), autologous stem cell therapy (ACST), and ALRV5XR act as activators of similar growth factor and cytokine subcellular routes, including the Wnt/β-catenin signaling pathway ( 1 , 2 , 7 ). Moreover, in a related but different matter, it can be observed that senescent alopecia (SA) and AGA display similar miniaturization and histologic features ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In any case, it has been noted that AGA-miniaturized vellus-like hairs, are not definitively influenced by these drugs; consequently, they cannot be converted back to THs ( 5 , 8 , 9 ). In contrast, ALRV5XR, a novel botanical natural product treatment for AGA, showed significant TH regrowth and appeared to reverse miniaturized hairs ( 12 , 13 ). Individuals affected by AGA seeking therapy would benefit from both a safe option aimed to prevent further hair loss and, potentially, a treatment that might regenerate their normal scalp hair phenotype.…”
Section: Introductionmentioning
confidence: 89%